My life as a villainess : essays - Lippman, Laura, 1959- (William Morrow, an imprint of HarperCollinsPublishers, 2020)
Collects the author's recent essays exploring motherhood as an older mom, her life as a reader, her relationships with her parents, her newspaper career, and her experiences as a novelist.